2010
DOI: 10.1086/651117
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between HIV/Highly Active Antiretroviral Therapy (HAART)–Associated Lipodystrophy Syndrome and Stavudine‐Triphosphate Intracellular Levels in Patients with Stavudine‐Based Antiretroviral Regimens

Abstract: Intracellular levels of d4T-TP are strongly associated with the development of HALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
6
32
0
1
Order By: Relevance
“…There is overwhelming epidemiological evidence linking d4T to the development of fat depot alterations (47). In this regard, our preliminary work, which needs further replication, suggests that a genetic mechanism may cause an alteration of nucleotide pools favoring an increase in d4T-TP levels, which we have found to be associated with the development of HALS in two different studies (11). This may explain why the TS genotype is also associated with the development of HALS (Table 2).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…There is overwhelming epidemiological evidence linking d4T to the development of fat depot alterations (47). In this regard, our preliminary work, which needs further replication, suggests that a genetic mechanism may cause an alteration of nucleotide pools favoring an increase in d4T-TP levels, which we have found to be associated with the development of HALS in two different studies (11). This may explain why the TS genotype is also associated with the development of HALS (Table 2).…”
Section: Discussionmentioning
confidence: 58%
“…To our knowledge, this is the first pharmacogenetic study that has demonstrated the involvement of the metabolic folate pathway in determining the levels of d4T-TP, which in turn have been associated with the appearance of HALS (11). Not unexpectedly, TS genotypes are also associated with the appearance of HALS as well.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…However, stavudine is rapidly cleared from the circulation, and the serum concentration-time curve is a poor predictor of the degree of mitochondrial toxicity and antiretroviral efficacy. Previous literature has revealed that the trough d4T-TP concentration determines the antiretroviral efficacy, while the peak d4T-TP concentration determines the degree of mitochondrial toxicity (31). A dose optimization should therefore aim to achieve an adequate d4T-TP trough (to retain efficacy) while reducing the peak d4T-TP concentration (to reduce toxicity).…”
Section: Discussionmentioning
confidence: 99%